ANALISIS TINGKATAN STRES DAN PENGARUHNYA TERHADAP KINERJA PIMPINAN CABANG BANK SWASTA NASIONAL DI SURABAYA - Purnomolastu, N. (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2004)
After facing some problems for the last few years and along with the monetary crisis in Indonesia, now days, especially concerning with the top management of bank, in running banking activities comes to surface. The activities are close to demand/ target assigned to them which surely affects their stress level. In the end, it also affects their performance. This research was conducted in June 2003 to private bank in Surabaya that enter into an alliance with